2008
DOI: 10.1002/anie.200704228
|View full text |Cite
|
Sign up to set email alerts
|

Contrasting cis and trans Effects on the Reactivity of Nonheme Oxoiron(IV) Complexes

Abstract: Position determines properties: The oxidative properties of [FeIV(O)(L)(X)] species (L=tetradentate N4 ligand, X=monodentate ligand) depend on the position of the X ligand. The FeO unit is a poorer oxidant with an electron‐donating cis ligand but becomes a much better oxidant when this ligand is trans to the oxo group. This difference in reactivity reflects perturbations to the electronic structure of the highly covalent FeO moiety.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 43 publications
(30 citation statements)
references
References 38 publications
0
30
0
Order By: Relevance
“…We followed the decay of 2 by UV/Vis spectrophotometry and observed the formation of a green species 4 with l max = 740 nm ( Figure S19 in the Supporting Information). This near-IR chromophore closely resembles low-spin L-Fe IV =O complexes generated by O À O bond homolysis of L-Fe III -A C H T U N G T R E N N U N G (OOH) intermediates supported by several polyamine-or aminopyridine ligands (L) analogous to bpmen, [33] suggesting that 4 can also be formulated as an Fe IV =O intermediate. This formulation is consistent with the EPR-silent nature of the green intermediate 4: it was found that 2 decayed over 70 s (k % 0.01 s À1 , RT) at room temperature without formation of any new EPR-active species ( Figure S20 in the Supporting Information).…”
Section: Fe III a C H T U N G T R E N N U N G (Ooh) Reactivity Pathwamentioning
confidence: 77%
“…We followed the decay of 2 by UV/Vis spectrophotometry and observed the formation of a green species 4 with l max = 740 nm ( Figure S19 in the Supporting Information). This near-IR chromophore closely resembles low-spin L-Fe IV =O complexes generated by O À O bond homolysis of L-Fe III -A C H T U N G T R E N N U N G (OOH) intermediates supported by several polyamine-or aminopyridine ligands (L) analogous to bpmen, [33] suggesting that 4 can also be formulated as an Fe IV =O intermediate. This formulation is consistent with the EPR-silent nature of the green intermediate 4: it was found that 2 decayed over 70 s (k % 0.01 s À1 , RT) at room temperature without formation of any new EPR-active species ( Figure S20 in the Supporting Information).…”
Section: Fe III a C H T U N G T R E N N U N G (Ooh) Reactivity Pathwamentioning
confidence: 77%
“…It has been found that ligand donor moieties in cis-position to the oxo unit (equatorial donors) exert less influence on the reactivity of Fe IV O (S = 1) octahedral complexes as compared to those ligated trans (axial) 48 as "trans-ligands can interact with both σ-and π-orbitals involved in the FeO bond but cis-ligands cannot". 53 However, in the present case, the effect of replacing equatorial pyridyl donors with (Nmethyl)benzimidazolyl units is quite significant. The (number and positions of) equatorial donors in octahedral complexes can modulate the spin state and reactivity of the oxo unit by altering the energies, and thus the occupancies, of the iron d xy and d x 2 −y 2 orbitals.…”
Section: ■ Discussionmentioning
confidence: 94%
“…20 This is partly due to the high stability of this complex, but also because ligands trans to the oxo unit have been found to exert a greater influence than those ligated cis . 21 This difference was attributed to the fact that trans ligands can interact with both σ- and π-type orbitals involved in the Fe=O bond but cis ligands cannot. Interestingly, whereas the complexes [Fe IV (O)(TMC)(X)] + ( 1-X , where X = monoanion) were found to display increased reactivity in O-atom transfer (OAT) with increasing electrophilicity, the reverse trend was found in hydrogen atom transfer (HAT).…”
Section: Introductionmentioning
confidence: 99%
“…pyridine N-oxide 21 ). This approach failed in all cases, presumably due to a combination of steric hindrance around the binding site and mass action (CH 3 CN was used as the solvent).…”
Section: Introductionmentioning
confidence: 99%